2021
DOI: 10.1111/pde.14513
|View full text |Cite
|
Sign up to set email alerts
|

Readability of online patient education materials for juvenile dermatomyositis

Abstract: In this study, we sought to analyze the readability of online patient education materials (PEMs) related to juvenile dermatomyositis (JDM). We analyzed the top 100 Google results and using six different readability scores, found 53 PEMs which had an average grade reading level of 17.4 (graduate level). PEMs by health care providers were written at higher grade levels than those by non-health care providers. Our findings demonstrate a clear need for online JDM PEMs that are written at an appropriate reading lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
1
4
0
Order By: Relevance
“…In this study, the 22 sites with online education materials related to vocal cord leukoplakia were written at readability levels above those recommended by the AMA/NIH. These results are consistent with many other readability studies that have been published within otolaryngology 7,8,20,28–33 and other specialties 34–43 …”
Section: Discussionsupporting
confidence: 91%
“…In this study, the 22 sites with online education materials related to vocal cord leukoplakia were written at readability levels above those recommended by the AMA/NIH. These results are consistent with many other readability studies that have been published within otolaryngology 7,8,20,28–33 and other specialties 34–43 …”
Section: Discussionsupporting
confidence: 91%
“…Reading level assessments to evaluate patient-facing materials can help determine if decision aids are written at a level that patients with limited health literacy levels are able to understand [11 ▪▪ ,15]. One study appraising online patient education material for juvenile dermatomyositis found that information, whether written by healthcare providers or nonhealthcare providers, was at a higher reading level than the average US resident's reading level of 8th grade; moreover, materials written by healthcare providers were at a higher level than those written by nonhealthcare providers [16]. Numeracy and electronic health literacy both impact comprehension, as well [7,17].…”
Section: Communicating Diagnosis and Treatment Informationmentioning
confidence: 99%
“…Numeracy and electronic health literacy both impact comprehension, as well [7,17]. Dermatology patient education materials commonly have reading levels significantly above the nationally recommended guidelines, particularly due to complex medical terminology [11 ▪▪ ,16,18–21]. A study looking at eczema action plans found that the mean reading level was three grades above the recommended reading level of 6th grade for materials geared toward the general population [18].…”
Section: Communicating Diagnosis and Treatment Informationmentioning
confidence: 99%
“…The most commonly cited tool in pediatric dermatology literature is the Flesch-Kincaid Readability Test. [2][3][4] This tool is also available in Microsoft ® Word and can be utilized directly in the document to determine reading levels. 7 Additional tools which calculate readability include the Fry Readability Graph, the Gunning 'FOG' Readability Test, and the Simple Measure of Gobbledygook Readability Formula.…”
Section: De Termining the Patient ' S Appropriate Re Ading Le Velmentioning
confidence: 99%
“…Furthermore, written materials dedicated to the pediatric population are often not at appropriate reading levels. 4 The psychosocial impact of pediatric skin diseases cannot be overlooked. Childhood skin conditions can negatively affect emotional health and self-esteem due to embarrassment and bullying, contributing to poor treatment adherence and development of psychiatric comorbidities.…”
mentioning
confidence: 99%